Metatranscriptomic analysis reveals the diversity of RNA viruses in ticks in Inner Mongolia, China. - Si Su; Meng-Yu Cui; Li-Li Xing; Rui-Juan Gao; Lan Mu; Mei Hong; Qi-Qi Guo; Hong Ren; Jing-Feng Yu; Xiao-Yan Si; Mutu Eerde (PLoS Neglected Tropical Diseases)
Background Ticks are widely distributed throughout China and are the second most prevalent pathogen vectors in the world, following only mosquitoes. Tick bites can lead to Lyme disease, forest encephalitis, and other illnesses that may result in death under severe circumstances. Materials and methods: Ticks collected from March 2021 to May 2023 were pooled and used in metatranscriptomic analyses to gain insight into the diversity and distribution of tick-borne viruses in Inner Mongolia. Next-generation sequencing (NGS) outcomes were validated, and viral prevalence across distinct tick species was determined through the application of polymerase chain reaction (PCR) paired with Sanger sequencing. Results A total of 20 RNA viruses belonging to at least 8 families, including Chuviridae, Flaviviridae, Solemoviridae, Nairoviridae, Partitiviridae, Phenuiviridae, Rhabdoviridae, and Totiviridae, and to unclassified families were identified by NGS. Five of the identified RNA viruses (Nuomin virus, Yezo virus, tick-borne encephalitis virus, Alongshan virus, and Beiji nairovirus) are considered human pathogens. A potential human pathogen, Mukawa virus, was also among the identified viruses. Ixodes persulcatus carried a significantly greater number of viral species than did Dermacentor nuttalli, Hyalomma marginatum, and Haemaphysalis concinna. The prevalence of coinfection with multiple viruses differed in I. persulcatus from Hinggan League and Hulun Buir, and Beiji nairovirus was the codominant virus species. Conclusions There is a remarkable diversity of RNA viruses harboured by ticks in Inner Mongolia, with variations observed in the distribution of these tick-borne viruses across different regions and tick hosts.